Religion and HIV Sexual Risk Among Men Who Have Sex With Men in China. (1st December 2016) - Pan, Stephen W.; Zhang, Zheng; Li, Dongliang; Carpiano, Richard M.; Schechter, Martin T.; Ruan, Yuhua; Spittal, Patricia M.
Abstract : Background: Religion can profoundly impact the sociocultural contexts that shape sexual HIV vulnerability among men who have sex with men (MSM). However, the relationship between religion and HIV vulnerability remains poorly understood for MSM in China, where religious affiliations and practices are rapidly increasing. Methods: Using cross-sectional survey data collected in Beijing and Tianjin, China, from 2013 to 2014 (n = 400), this study tests 3 hypotheses regarding religion and HIV sexual risk: (1) HIV vulnerabilities and testing patterns among religiously affiliated MSM are lower than for areligious MSM, (2) religiosity is inversely associated with HIV vulnerabilities and testing, and (3) the magnitude of inverse association between religiosity and HIV vulnerabilities/testing will be stronger among Christian and Muslim MSM than Buddhist and areligious MSM. Results: Compared with areligious participants, Buddhists had higher odds of reporting unprotected anal intercourse [adjusted odds ratio (AOR): 2.06, 95% confidence interval (CI): 1.13 to 3.75] and more male sex partners (AOR: 1.95, 1.16–3.27), whereas Muslims had lower odds of reporting unprotected anal intercourse (AOR: 0.33, 95% CI: 0.15 to 0.73) and higher odds of reporting male circumcision (AOR: 3.04, 95% CI: 1.45 to 6.40). Reporting of forced sex was associated with more frequent participation in social religious activities (AOR: 1.25, 95% CI: 1.02 to 1.52) and private religious activities (AOR: 1.30, 95% CI: 1.04 to 1.61). Among Christians, participation in private religious activities was associated with lower odds of reporting anal intercourse (AOR: 0.49, 95% CI: 0.27 to 0.88). Conclusions: The sustained growth of multiple religious traditions in China appears to have important implications for HIV vulnerability among religious minority MSM.